A retrospective study of obstetric hysterectomy cases at tertiary care centre - Joshi, Khushi P.; Shah, Sapana R.; Agrawal, Saumya P.; Goswami, Vishwa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Postpartum haemorrhage (PPH) is a life-threatening condition. The objective of this study was to determine the incidence, demographic characteristics, indications, and feto-maternal outcomes associated with obstetric hysterectomy in a tertiary care centre. Methods: This is a retrospective analytical study conducted over a period of six years, from March 2014 to April 2020. A total of 68 cases of obstetric hysterectomy were studied at tertiary care centre in Ahmedabad, Gujarat, India. Results: Present study reported 68 obstetric hysterectomies per 44663 total deliveries (incidence - 0.15%), out of them 20 following 26446 vaginal deliveries (0.07%) and 48 following 18217 caesarean section (0.26%). Morbidly adherent placenta (29.41%) was the most common indication followed by atonic postpartum haemorrhage (25.00%) and uterine rupture (17.64%). The most frequent sequelae were disseminated intravascular coagulation (26.47%) and febrile morbidity (10.29%), maternal mortality was 16.17% whereas neonatal mortality was 26.47%. Conclusions: The incidence of obstetric hysterectomy has been found to be more following caesarean sections. There is a change in the indications of obstetric hysterectomy in the past two decades with placenta accreta spectrum being the commonest in present study. This is because of rising number of caesarean sections. Patients who underwent emergency obstetric hysterectomy due to atonic PPH had a higher mortality.